2011
DOI: 10.1039/c1cp20502a
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of the influence of reducible iron(iii) metal sites on the adsorption of CO, CO2, propane, propene and propyne in the mesoporous metal–organic framework MIL-100

Abstract: The present study illustrates the importance of the oxidation state of iron within the mesoporous iron trimesate [{Fe(3)O(H(2)O)(2)F(0.81)(OH)(0.19)}{C(6)H(3)(CO(2))(3)}(2)] denoted MIL-100(Fe) (MIL= Material from Institut Lavoisier) during adsorption of molecules that can interact with the accessible metal sites through π-back donation. Adsorption of CO has been first followed by FTIR spectroscopy to quantify the Lewis acid sites in the dehydrated Fe(III) sample, outgassed at 150 °C, and on the partially redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
282
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 217 publications
(315 citation statements)
references
References 49 publications
31
282
2
Order By: Relevance
“…It was observed that this activation treatment does not influence the performance of MIL-101(Cr), while the activity for MIL-101(Fe) increases upon activation. It has been reported that under these activation conditions Fe 3+ becomes reduced to Fe 2+ in MIL-101(Fe), [51][52][53] while this reduction process has not been observed for the case of MIL-101(Cr). 12 Also, coordinated water is easier desorbed from MIL-101(Fe) than in MIL-101(Cr).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that this activation treatment does not influence the performance of MIL-101(Cr), while the activity for MIL-101(Fe) increases upon activation. It has been reported that under these activation conditions Fe 3+ becomes reduced to Fe 2+ in MIL-101(Fe), [51][52][53] while this reduction process has not been observed for the case of MIL-101(Cr). 12 Also, coordinated water is easier desorbed from MIL-101(Fe) than in MIL-101(Cr).…”
Section: Resultsmentioning
confidence: 99%
“…Since the structure of Mn-MIL-100 is composed of trimeric units of corner-sharing octahedra {Mn 3 (µ 3 -O)(H 2 O) 3 (O 2 C-R) 6 } the formation of other 15 MOFs which are also based on this inorganic building units could be possible.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the in-situ formation of Mn 3+ ions 15 by oxidation of Mn 2+ ions in the synthesis of MOFs has not been described previously. Therefore, the reaction conditions were investigated in detail.…”
Section: Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…P/P0 = 0.06 and 0.12 can be distinguished from the isotherms of MIL-100(Fe) and MIL-100(Cr). Textural properties of all catalysts are summarized in Table 1 The investigations of Lewis acidity of MOFs [55,56] and demonstration of correlations between amount of Lewis acid sites and catalytic activity of MOFs [57] are rather limited.…”
Section: Structure and Textural Properties Of Mofsmentioning
confidence: 99%